Experimental Analysis of the Counterfactuals Elaboration in an Election Task - Cárdenas Leroy, Germán; Instituto Tecnológico de Estudios Superiores de Occidente (Pontificia Universidad Javeriana, 2009)
Counterfactuals are statements that raise alternatives to past events (Roese, 1997). The objective of the present research was to analyze if functional connections between counterfactuals and behaviour were observed, when humans subjects were exposed to an election task with risk. An experimental preparation was designed in which the elaboration of counterfactuals was promoted or blocked. The study was carried out with college students. The results showed that most of the participants exposed to conditions that promoted the elaboration of counterfactual statements, modified their behaviour from an experimental condition to the other one, whereas the majority of individuals exposed to conditions that interfered with counterfactual elaboration did not.